Legal assessment of applicability of the provisions of Article 239.1 of the Civil Code of the Russian Federation in time and constituency - V.A. Petrushkin (Ученые записки Казанского университета: Серия Гуманитарные науки)
The provisions of Article 239.1 of the Civil Code of the Russian Federation were analyzed through various versions of the law in force at different periods. The dynamics of development of law enforcement practices was considered. The research is based on a thorough investigation of the judicial practices and the clarifications from higher courts. It was suggested that there are problems in the current law enforcement practices regarding the scope of persons, to whom the rules on the seizure and sale of unfinished construction objects are applied. The need to resolve the issues on applicability of Article 239.1 of the Civil Code of the Russian Federation in time and concerning users of the land owned by the state or municipal authorities by means of various legal methods and official clarifications by the Supreme Court of the Russian Federation was substantiated. Based on the obtained results, a fair and logical idea was introduced that the objective of civil and land legislation is to ensure legal certainty in relation to state-owned land plots that cannot be re-granted for completion of construction without bidding to persons, who failed to complete the construction project.